Reconstruction of a Shotgun Injury: A Case Review - Selvi L T, Kalai; Rayamane, Anand P; Kumar M V, Pradeep; R, Punitha; C, Chandrashekaraiah; B C , Ravindra (Journal of Indian Academy of Forensic Medicine, 2014)
Every firearm case is unique in the sense that the behavior of the missile from the movement it leaves the gun barrel till it ends its journey. According to the internal ballistics interpretation of which is the task before carrying post-mortem examination, of every firearm injury is very interesting and specific to the case. This is so because of innumerable variables affecting the entire process. Crime scene reconstruction is the process of determining or eliminating the events and actions that occurred at the crime scene through analysis of the crime scene pattern, the location and position of the physical evidence including deceased body and the autopsy findings and laboratory examination of the physical evidence. Here with we are reviewing case of muzzle loading shotgun injury resulting in death in which investigating officer has suspicion about death as deceased sustained multiple firearm injuries. This case highlights the importance of posture of the victim interpreting the resultant injuries and recreating the scene of occurrence. A meticulous autopsy, examination of weapon and reconstruction of scene of crime in order to elucidate the manner of death are of great importance in firearm cases.